THE EFFECT OF SEALING PROCESSES ON THE CORROSION BEHAVIOUR OF Al₂O₃-13 WT.%TiO₂ COATING - Jia Shao; Zehua Wang; Si Liqiong; Zhou Zehua; Zhang Xin; Jiang Shaoqun; Wang Gang (Ceramics-Silikáty, 2019)

(untitled)
A novel post-treatment process was employed to seal a plasma-sprayed Al₂O₃-13wt. %TiO₂ (AT13) coating to improve its corrosion resistance. A series of AT13 coatings were sealed with silicone resin using conventional sealing and ultrasonic sealing at different temperatures. The effect of the sealing treatment on the corrosion behaviours of the coatings were investigated with salt spray tests and electrochemical methods. Most of the ultrasonic sealed coatings had less weight loss than conventional sealed coatings after the salt spray test. In 5.0 wt. % NaCl solutions, the ultrasonic sealed coating had the higher corrosion potential and the lower corrosion current density. The coating sealed at 40℃ has the lowest corrosion weight loss, lowest corrosion current densities and highest corrosion potential, compared with conventional sealed coating. It means that ultrasonic sealing can improve the corrosion resistance of plasma-sprayed AT13 coating effectively and the temperature was a key factor in the sealing treatment.